2020
DOI: 10.1016/j.jvsv.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes of a Randomized Trial of Treatments for Varicose Veins

Abstract: BACKGROUND Endovenous laser ablation and ultrasound-guided foam sclerotherapy are recommended alternatives to surgery for the treatment of primary varicose veins, but their long-term comparative effectiveness remains uncertain. METHODS In a randomized, controlled trial involving 798 participants with primary varicose veins at 11 centers in the United Kingdom, we compared the outcomes of laser ablation, foam sclerotherapy, and surgery. Primary outcomes at 5 years were disease-specific quality of life and generi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…In a 2019 RCT of patients with severe varicose veins, quality of life 5 years after treatment assessed with the Varicose Vein Questionnaire was better after laser ablation (effect size, −2.86 [95% CI, −4.49 to −1.22]) or surgery (effect size, −2.60 [95% CI, −3.99 to −1.22]) than after foam sclerotherapy. 92 The success of these procedures is critically compromised according to the progressive increase in weight, especially in those with a BMI ≥ 35 kg/m 2 . 93…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…In a 2019 RCT of patients with severe varicose veins, quality of life 5 years after treatment assessed with the Varicose Vein Questionnaire was better after laser ablation (effect size, −2.86 [95% CI, −4.49 to −1.22]) or surgery (effect size, −2.60 [95% CI, −3.99 to −1.22]) than after foam sclerotherapy. 92 The success of these procedures is critically compromised according to the progressive increase in weight, especially in those with a BMI ≥ 35 kg/m 2 . 93…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…However, PCF was limited in its clinical efficacy and overall safety profile. 19,20 PEM was developed to eliminate the physical properties of PCF that led to neurological and cardiac adverse events including inconsistent bubble size and nitrogen bubbles that lead to gas embolism. 8,11,[20][21][22][23][24] In our practice, the main treatment has been EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 PEM was developed to eliminate the physical properties of PCF that led to neurological and cardiac adverse events including inconsistent bubble size and nitrogen bubbles that lead to gas embolism. 8,11,[20][21][22][23][24] In our practice, the main treatment has been EVLA. However, in most patients, there is a requirement to introduce a second treatment modality to reach smaller veins, tortuous veins, or areas of the leg that present with venous ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…These MIT have consistently been reported to reduce trauma, improve aesthetic outcomes, and expedite recovery compared to traditional surgical modalities. Although multiple studies have demonstrated the long-term efficacy of MIT (12,13), additional research is necessary to confirm their sustained effectiveness (10,14).…”
Section: Introductionmentioning
confidence: 99%